The effect of outside-school learning courses on prospective teachers’ aims of performing outside-school learning activities - MERTOĞLU, HATİCE (My University, 2023)
One of the methods used in educating 21st-century individuals is outside-school learning. This article investigates the effect of outside-school learning courses on teacher candidates’ aims of performing outside-school learning activities. The research uses single group pre-test and post-test design. The participants of the research are 37 prospective teachers studying at the 3rd grade of the Department of Mathematics and Science Teaching of a state university in Istanbul during the fall semester of the 2016-2017 academic year. The purposive sampling method is used to determine the study group. "Outside School Learning Activities Performability Scale" developed by Karademir (2013) is used as a data collection tool in the study. According to the study findings, an increase is observed in all dimensions in favor of the post-test. Additionally, it is determined that there is a statistically crucial difference in the Behavioral Expectation, Behavioral Assessment, Behavioral Easiness, Expectations of Individuals, Institutions and Organizations and Special Norm dimensions. These dimensions are the factors that affect behavior as attitude against behavior, subjective form and perceived behavior control. When all the results are evaluated together, it can be said that the outsideschool learning course positively affects teacher candidates’ aims of performing outside-school learning activities.
Keywords: Outside-School Learning; Teacher Candidates; Science Teaching; Outside-School Activities